Effects of high‐intensity exercise training on physical fitness, quality of life and treatment outcomes after oesophagectomy for cancer of the gastro‐oesophageal junction: PRESET pilot study. Issue 5 (28th August 2020) - Simonsen, C.; Thorsen‐Streit, S.; Sundberg, A.; Djurhuus, S. S.; Mortensen, C. E.; Qvortrup, C.; Pedersen, B. K.; Svendsen, L. B.; de Heer, P.; Christensen, J. F.
Abstract : Background: Treatment for cancer of the gastro‐oesophageal junction (GOJ) can result in considerable and persistent impairment of physical fitness and health‐related quality of life (HRQoL). This controlled follow‐up study investigated the feasibility and safety of postoperative exercise training. Methods: Patients with stage I–III GOJ cancer were allocated to 12 weeks of postoperative concurrent aerobic and resistance training (exercise group) or usual care (control group). Changes in cardiorespiratory fitness, muscle strength and HRQoL were evaluated. Adherence to adjuvant chemotherapy, hospitalizations and 1‐year overall survival were recorded to assess safety. Results: Some 49 patients were studied. The exercise group attended a mean of 69 per cent of all prescribed sessions. After exercise, muscle strength and cardiorespiratory fitness were increased and returned to pretreatment levels. At 1‐year follow‐up, the exercise group had improved HRQoL (+13·5 points, 95 per cent c.i. 2·2 to 24·9), with no change in the control group (+3·7 points, −5·9 to 13·4), but there was no difference between the groups at this time point (+9·8 points, −5·1 to 24·8). Exercise was safe, with no differences in patients receiving adjuvant chemotherapy (14 of 16 versus 16 of 19; relative risk (RR) 1·04, 95 per cent c.i. 0·74 to 1·44), relative dose intensity of adjuvant chemotherapy (mean 57 versus 63 per cent; P = 0·479), hospitalization (7 of 19 versus 6 of 23; RR 1·41, 0·57 to 3·49) or 1‐year overall survival (80 versus 79 per cent; P = 0·839) for exercise and usual care respectively. Conclusion: Exercise in the postoperative period is safe and may have the potential to improve physical fitness in patients with GOJ cancer. No differences in prognostic endpoints or HRQoL were observed. Registration number: NCT02722785 ( https://www.clinicaltrials.gov ). Abstract : With concurrent aerobic exercise and resistance training twice a week during treatment, patients with cancer of the gastro‐oesophageal junction can return cardiopulmonary fitness and muscle strength to pretreatment levels at completion of treatment. This can be done without affecting prognostic endpoints and with positive effects on health‐related quality of life. Generally well tolerated and safe. Abstract : Antecedentes: El tratamiento del cáncer de la unión gastroesofágica ( gastroesophageal junction, GEJ) puede determinar un deterioro considerable y persistente de la condición física y de la calidad relacionada con la salud ( health‐related quality of life, HRQoL). El objetivo de este estudio controlado de seguimiento fue investigar la factibilidad y seguridad del entrenamiento físico postoperatorio. Métodos: Pacientes con cáncer de GEJ en estadio I‐III fueron asignados a 12 semanas de entrenamiento postoperatorio simultáneo aeróbico y de resistencia o a cuidados médicos habituales. Se evaluaron los cambios en el estado cardiorrespiratoria, fuerza muscular y HRQoL. Se recogieron datos de la adherencia a la quimioterapia adyuvante, hospitalizaciones y supervivencia global a 1 año para evaluar la seguridad. Resultados: Se estudiaron un total de 49 pacientes. El grupo con ejercicio asistió al 69% de todas las sesiones planificadas. Después del ejercicio, la fuerza muscular y el estado cardiorrespiratorio aumentaron y volvieron a los niveles previos al tratamiento. Si bien al año de seguimiento, el grupo con ejercicio presentó una mejoría de la HRQoL (+13, 5 puntos (i.c. del 95% 2, 2 a 24, 9)), sin cambios en el grupo con atención médica habitual (+3, 7 puntos (i.c. del 95% −5, 9 a 13, 4)), no hubo diferencias entre los grupos en ese momento (+9, 8 puntos (i.c. del 95% −5, 1 a 24, 8)). El ejercicio fue seguro, sin diferencias entre el ejercicio o la atención médica habitual en pacientes que recibían quimioterapia adyuvante 87, 5% versus 84, 2% (RR 1, 04 (i.c. del 95% 0, 74 a 1, 44)), intensidad relativa de la dosis de quimioterapia adyuvante 56, 8% versus 63, 3% ( P = 0, 479), hospitalizaciones 36, 8% versus 26, 1% (RR 1, 41 (i.c. del 95% 0, 57 a 3, 49)) o supervivencia global a 1 año 80, 0% versus 79, 3% ( P = 0, 839). Conclusión: El ejercicio en el periodo postoperatorio es seguro y puede tener potencial para mejorar la condición física en pacientes con cáncer de GEJ. No se observaron diferencias en los resultados pronósticos o en la HRQoL.